Association of a Large Panel of Cytokine Gene Polymorphisms with Complications and Comorbidities in Type 2 Diabetes Patients - Rodrigues, K. F.; Pietrani, N. T.; Sandrim, V. C. [UNESP]; Vieira, C. M. A. F.; Fernandes, A. P.; Bosco, A. A.; Gomes, K. B. (Hindawi Publishing Corporation, 2015)
Aims. The polymorphisms of pro- and anti-inflammatory cytokines may be involved in type 2 diabetes (T2D) pathogenesis and its complications. Methods. We investigated in 102 T2D patients the association of the cytokine polymorphisms in the TNF-alpha, IL-10, IL-6, TGF-beta 1, and IFN-gamma genes with the T2D microvascular complications and comorbidities (hypertension, dyslipidemia, and obesity). Cytokine genotypes were determined by PCR using Cytokine Genotyping Tray kit. Results. Diabetic retinopathy was associated with GG genotype and G allele in TGF-beta 1 codon 25C/G polymorphism (p = 0.004 and.. = 0.018) and the nephropathy was associated the lower frequency of GG genotype in IL-10-1082G/A polymorphism (p = 0.049). Hypertension was associated with the CC genotype and C allele for IL-10 -592C/A polymorphism (p = 0.013 and p = 0.009) and higher frequencies of T (p = 0.047) and C (p = 0.033) alleles of the TGF-beta 1 codon 10T/C and IL-10-819T/C polymorphisms, respectively. The TGF-beta 1 codon 10T/C polymorphismwas associated with the BMI groups (p = 0.026): the CC genotype was more frequent in the group with BMI < 25Kg/m(2), while the TC genotype was more frequent in the group with BMI = 30 Kg/m(2). Conclusions. Our findings suggest that TGF-beta 1 and IL-10 polymorphisms are involved in complications and comorbidities in T2D patients.